Combating misinformation online: Re-imagining social media for policy-making - Eleni A. Kyza; Christiana Varda; Dionysis Panos; Melina Karageorgiou; Nadejda Komendantova-Amann; Serena Coppolino Perfumi; Syed Iftikhar Husain Shah; Akram Sadat Hosseini (Internet Policy Review, 2020)
Social media have created communication channels between citizens and policymakers but are also susceptible to rampant misinformation. This new context demands new social media policies that can aid policymakers in making evidence-based decisions for combating misinformation online. This paper reports on data collected from policymakers in Austria, Greece, and Sweden, using focus groups and in-depth interviews. Analyses provide insights into challenges and identify four important themes for supporting policy-making for combating misinformation: a) creating a trusted network of experts and collaborators, b) facilitating the validation of online information, c) providing access to visualisations of data at different levels of granularity, and d) increasing the transparency and explainability of flagged misinformative content. These recommendations have implications for rethinking how revised social media policies can contribute to evidence-based decision-making.
Keywords: 300; Misinformation; Policy-making; Internet policy; Social media